2021
DOI: 10.5430/jer.v6n1p35
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance of Escherichiacoli and Salmonella isolated from retail broiler chicken carcasses in Zambia

Abstract: Antimicrobial resistance (AMR) of foodborne pathogens is of public health concern, especially in developing countries such as Zambia. This study was undertaken to determine the antimicrobial resistance profiles of Escherichia coli (E. coli) and Salmonella isolated from retail broiler chicken carcasses purchased from open markets and supermarkets in Zambia. A total of 189 E. coli and five Salmonella isolates were isolated. Identification and confirmation of the isolates were done using Analytical Profile Index … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Phiri et al observed the prevalence of AMR to be 94.6% and resistance to tetracycline (81.4%), sulfamethoxazole/trimethoprim (65.4%), and ampicillin (72.9%) among E. coli isolates from broilers at abattoirs and open markets ( 11 ). Similarly, Muligisa-Muonga et al found prevalence of AMR to be 88% and resistance to tetracycline (79.4%), sulfamethoxazole/trimethoprim (49.7%), and ampicillin (51.9%) of E. coli isolates from retail broiler carcasses ( 12 ).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Phiri et al observed the prevalence of AMR to be 94.6% and resistance to tetracycline (81.4%), sulfamethoxazole/trimethoprim (65.4%), and ampicillin (72.9%) among E. coli isolates from broilers at abattoirs and open markets ( 11 ). Similarly, Muligisa-Muonga et al found prevalence of AMR to be 88% and resistance to tetracycline (79.4%), sulfamethoxazole/trimethoprim (49.7%), and ampicillin (51.9%) of E. coli isolates from retail broiler carcasses ( 12 ).…”
Section: Discussionmentioning
confidence: 96%
“…Broiler chickens traded on the market were either processed at a recognized slaughter facility or at the home of the farmer, particularly done by back yard farmers. Chickens processed at home posed a relatively higher risk of carrying AMR pathogens than those processed in a slaughter facility because of increased likelihood of cross-contamination resulting from unhygienic processing conditions ( 11 , 12 , 34 ). The cross contamination and spread of AMR microorganisms to the environment and the public, in general, could also be due to the marketing of live birds at local open markets and roadside stalls, with limited sanitation, where humans and food animals interface ( 38 41 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 65 Besides, E. coli isolates from wildlife and livestock were highly resistant to ampicillin (27%), ceftazidime (14.3%), cefotaxime (9.5%) and kanamycin (9.5%). 66 In these animal species, a prevalence of 36.5% MDR was reported in broilers 63 % and 18.8% in wildlife. 66 However, the study of the prevalence and AMR profiles of E. coli isolated from laying hens in Zambia was not reported prior to this study.…”
Section: Introductionmentioning
confidence: 97%
“…In Zambia, antimicrobial-resistant E. coli have been isolated from humans, 61 , 62 broiler chickens, 63 , 64 dairy 65 and wildlife and livestock. 66 In broilers, E. coli , was observed to be resistant to tetracycline, ampicillin, cotrimoxazole and ciprofloxacin, whereas, in dairy, it was resistant to tetracycline, ampicillin, cotrimoxazole and ciprofloxacin.…”
Section: Introductionmentioning
confidence: 99%